An ecological systems approach to family narratives. (July 2016) - Fivush, Robyn; Merrill, Natalie
We propose an ecological systems approach to family narratives that describes three dynamically interacting systems of family narratives: shared family narratives, communicative family narratives, and family history. We review developmental research on family storytelling within each of these levels and describe how they interact to create individual narrative identity, focusing on adolescence.